What could be a cancer mission objective if we join our forces in the fight against cancer?. Issue 6 (December 2019) - Philip, Thierry; Karjalainen, Sakari; De Lorenzo, Francesco; Apostolidis, Kathi; Lombardo, Claudio; Nilbert, Mef; Lacombe, Denis; Poortmans, Philip; Albreht, Tit; Kearns, Pamela; Vassal, Gilles
The European cancer burden is growing rapidly, with an estimated 2 million deaths a year according to the latest research. As almost half of cancers are diagnosed after the age of 65, and considering the aging European population, a tidal wave of cancer cases will sweep across Europe within the coming decades. Without major action, the additional number of annual cancer cases is expected to rise from 4.2 million to 5.2 million by 2040. If we are to reach plateauing numbers by 2040 (as a minimum goal), this would require 0.75% annual reduction in risk and 1% reduction in risk of death. These challenges call for attack from various angles, coordinated efforts, rational strategies, initiatives throughout the cancer trajectory, activities to reduce inequities, and implementation of evidence-based measures. In order to defeat the societal challenges of cancer through innovation, Europe will need to join forces and connect the European Commission and the member states, politicians and citizens, industries and patient associations. A cancer mission should thus unite the public and patient viewpoint to the perspective of cancer professionals. The authors describe a plan that has been agreed upon among some of the major European Cancer organizations and associations. This plan uses a cancer mission as a tool and must deliver robust medical evidence to patients and doctors through high-quality research delivering sustainable and affordable strategies for prevention, treatment, and follow-up.